Hybrid surgery versus endovascular intervention for patients with chronic internal carotid artery occlusion: A single-center retrospective study - Sun, Tao; He, Yiming; Wang, Fei; Mao, Bo; Han, Mengtao; Zhao, Peng; Wu, Wei; Wang, Yunyan; Li, Xingang; Wang, Donghai (Frontiers in Surgery, 2022)
Objective: Chronic internal carotid artery occlusion (CICAO) can cause transient ischemic attack (TIA) and ischemic stroke. Carotid artery stenting (CAS) with embolic protection devices and hybrid surgery combining carotid endarterectomy and endovascular treatment are effective methods for carotid revascularization. The objective of this study was to evaluate and compare the effect and safety of the two surgical procedures. Methods: This was a single-center retrospective study. In this study, 44 patients who underwent hybrid surgery and 35 who underwent endovascular intervention (EI) at our center were enrolled consecutively between May 2016 and March 2022. All patients were classified into four groups (A-D), as described by Hasan et al. We recorded and analyzed clinical data, angiographic characteristics, technical success rate, perioperative complications, and follow-up data. Results: There was no significant difference in baseline characteristics between hybrid surgery group and EI group, except for plasma high density lipoproteins (HDL) levels (median [interquartile range]: hybrid surgery, 0.99 [0.88-1.18] vs. EI, 0.85 [0.78-0.98] mmol/L, P = 0.001). The technical success rate of hybrid surgery was higher than that of EI (37/44 [84.1%] vs. 18/35 [51.4%], P = 0.002; type A: 15/16 [93.8%] vs. 10/11 [90.9%], P = 1.000; type B: 9/10 [90.0%] vs. 5/7 [71.4%], P = 0.537; type C: 12/15 [80.0%] vs. 3/12 [25.0%], P = 0.004; type D: 1/3 [33.3%] vs. 0/5 [0%], P = 0.375). No significant difference was observed in the incidence of perioperative complications between the two procedures (hybrid surgery: 7/44 [15.9%] vs. EI: 6/35 [17.1%], P = 0.883). In addition, there were no significant differences in the rates of stroke and restenosis during follow-up. Conclusions: For patients with symptomatic CICAO, hybrid surgery may have an advantage over EI in successfully recanalizing occluded segments. There was no significant difference in safety and restenosis between hybrid surgery and EI.